2017
DOI: 10.1177/1049732317731317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Powerlessness Among Health Care Workers in Tuberculosis Infection Control

Abstract: Due to their occupational exposure in health care settings, health care workers (HCW) have increased risk of Mycobacterium tuberculosis infection. They face challenges to remain up-to-date with evidence-based clinical practices and translate educational information into actions in infection control practices. Our purpose was to examine this "knowledge-action" gap about how HCWs understand their occupational M. tuberculosis risk and use recommended infection control measures in clinical practices in the Dominic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 34 publications
1
44
0
5
Order By: Relevance
“…Con respecto al personal de salud, otros autores han mencionado el riesgo de infección de TB que tienen estos trabajadores durante la atención de los pacientes con la enfermedad activa, por lo que es necesario implementar medidas administrativas y protección personal; además mencionan la importancia de mejorar la competencia y conocimiento en este personal (Ahmed, Aro, y Sodemann, 2009;Chapman et al, 2017). Los hallazgos de esta investigación indican que se tiene poco recurso en los centros de salud y muchas veces el personal de salud debe trabajar en lugares hacinados, sin poder separar a quienes padecen de diferentes patologías en otros salones, a pesar de que la política establezca condiciones para el aislamiento de estas personas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Con respecto al personal de salud, otros autores han mencionado el riesgo de infección de TB que tienen estos trabajadores durante la atención de los pacientes con la enfermedad activa, por lo que es necesario implementar medidas administrativas y protección personal; además mencionan la importancia de mejorar la competencia y conocimiento en este personal (Ahmed, Aro, y Sodemann, 2009;Chapman et al, 2017). Los hallazgos de esta investigación indican que se tiene poco recurso en los centros de salud y muchas veces el personal de salud debe trabajar en lugares hacinados, sin poder separar a quienes padecen de diferentes patologías en otros salones, a pesar de que la política establezca condiciones para el aislamiento de estas personas.…”
Section: Discussionunclassified
“…Los hallazgos de esta investigación indican que se tiene poco recurso en los centros de salud y muchas veces el personal de salud debe trabajar en lugares hacinados, sin poder separar a quienes padecen de diferentes patologías en otros salones, a pesar de que la política establezca condiciones para el aislamiento de estas personas. Aunado a esto, el personal no percibe la importancia de su trabajo para el diagnóstico y manejo de la TB, lo mismo se encontró en otro estudio (Chapman et al, 2017).…”
Section: Discussionunclassified
“…There were no studies that were of sufficiently poor quality to warrant exclusion from this review. [8,27]. The nationwide study from Romania reported an underdeveloped system for reporting TB amongst healthcare workers [13].…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…Poor funding and insufficient resources were the theme by far most frequently mentioned across all studies. Healthcare workers cited poor infrastructure, such as a lack of isolation space [17,24], poor clinic layout [28], windows opening in the wrong direction [29], and being unable to maintain equipment such as extractor fans as barriers to implementing isolation or environmental measures [17,19,26,27,30]. Because of insufficient funding to hire more staff, overstretched healthcare workers viewed cough screening, isolation and patient education as additional, non-essential tasks [14,17,19,22,30,31].…”
Section: Combined Qualitative and Quantitative Data Analysismentioning
confidence: 99%
See 1 more Smart Citation